A study of noise control at Kuala Lumpur International Airport (KLIA) / Norazlina Omar - Omar, Norazlina (2006)
This academic exercise is to give a clear understanding about the noise control at Kuala Lumpur International Airport (KLIA). The aim to this study is to know and find out about the noise level and do the sound test at Kuala Lumpur International Airport (KLIA). The test will do personally by guarding with the staff at the airport. The test will do from outside to inside and to inside to outside of the Main Terminal Building and The Hotel Building. The greatest design and the good use of the absorption materials can give the comfortable for the users. This is to know the sound level that received by the airport in any sources. The researcher gathered data from the parties who related such as technical department, officer etc. Then the findings will be analysis by the writer.